A Video Frame Indexing Based Frame Select Method - Sun, Chao; Liu, Yukun; Shouda, Jiang (2008 4th IEEE International Conference on Circuits and Systems for Communications, 2008)
In order to solve the precision guidance problem in television guidance missile system which is caused by time difference between the video frame used by the console and the video frame used by the guided missile. This paper proposes a novel video frame indexing based frame select method for television guidance system. By storing previous video frames and recording their indexing numbers, the same frame can be achieved on both the console and the guided missile. Compare with common selecting method, the proposed method can generate the tracking images more precisely.